ANALISIS PENGARUH VARIABEL MAKROEKONOMI TERHADAP PROFITABILITAS PADA PERUSAHAAN PERTAMBANGAN - seno hadi saputro (Universitas Bina Sarana Informatika, 2019)
The company’s survival is influenced by many things, among others is profitability of the company. The company’s profitability is determined by various factors, one of which is an external factor. External factor are beyond the company’s difficult part is controlled by the company. Macroeconomic factor are the external factors of the company. This study was conducted to evaluate the effect of GDB, BI Rate, Inflation and the exchange rate on the profitability of mining companies. The population using a mining company in Indonesia stock exchange in 2014-2018. Methodology research as the sample used purposive sampling technique sampling with particular determination in order to obtain a representative sample according to the sample criteria that will be used. Detrmination of sampling techniques was obtained 34 mining companies. Data were analyzed using multiple regression method data panel random effect. The result obtained showed the BI Rate has a negative effect on the profitability of mining companies, namely when the BI Rate is low, the company’s ability to fund its investment will increase. Whereas GDB, Inflation and exchange rate does not affect the profitability of mining companies.